Dampak Pemberian Subsidi Reboisasi Hutan kepada Pemerintah Provinsi terhadap Deforestasi di Indonesia - Trisnu Surandoko (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
This study investigates the impact of the forest subsidy on deforested area. Panel data used to examine whether the forest subsidy and the logging tariff policy can curb the deforested area in the province from 2009 to 2019. Pooled OLS was the suitable model to estimate the relationship. The study found unexpected result that the increase in forest subsidy increased the deforested area in a province. Whereas the increase in industry-manufacturing sector worker reduced the deforested area. Another unpredictable result was the logging tariff, which is expected to reduce deforested areas, did not affect the deforested area in a province.